Studies on vertical transmission of Trichinella spiralis in experimentally infected guinea pigs (Cavia porcellus) - Riva, Eliana (2017)
An experimental study to enhance knowledge on the capability of Trichenella spiralis to pass from guinea pigs to progeny at different periods of pregnancy or lactation was performed. For this purpose, 18 female adult guinea pigs were inoculated with 100 or 1000 T. spiralis muscle larvae (ML) during early, late gestation and during lactation period. The presence of T. spiralis (ML) in mothers and newborns was studied through enzymatic digestion from muscle samples. ML were observed in 9 of 42 newborn guinea pigs and levels of infection were significantly higher when infections of mothers were done during late gestation (p = 0.0046) with the high infective dose (p = 0.0043). T. spiralis ML were not recovered from any of the newborns from mothers infected in the lactation period. Ten out of 18 infected mothers presented larvae 1 in their mammary glands. Muscle samples from the tongue and the masseter showed the highest larval burdens. These observations confirm previous reports on that ML of T. spiralis are capable to pass through placental tissues to reach and encyst in striated muscle groups of newborn guinea pigs. This study may also reinforce the importance of preventive programs to control trichinellosis in those endemic areas where pregnant women would have high risk of infection.